2018
DOI: 10.1038/s41598-018-30631-2
|View full text |Cite
|
Sign up to set email alerts
|

Flt3 ligand treatment reduces enterovirus A71 lethality in mice with enhanced B cell responses

Abstract: Enterovirus A71 (EV-A71) infection can induce encephalitis, which causes death or long-term neurological sequelae, especially in young children. Using a murine infection model, we searched for anti-EV-A71 agents, because effective therapies are not available to control fatal infection. In EV-A71-infected mice, treatment with the hematopoietic growth factor, Fms-like tyrosine-kinase 3 ligand (Flt3 ligand) before infection reduced the lethality and tissue viral loads. Flt3 ligand failed to enhance the production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
(63 reference statements)
0
1
0
Order By: Relevance
“…Previous reports of IL-20RA cytokines mostly focused on T cells to show that IL-19 or IL-20 can increase IL-10 and/or decrease IFN-γ to induce T cell polorazation toward a Th2 pro le [19][20][21]. We previously found that T cell responses, especially the Th2 response, promote the production of antibodies, which protect mice from EV-A71 infection [45][46][47], and that the Th2 cytokine IL-6 decreases EV-A71 lethality of mice [30], showing the protective role of Th2 response in EV-A71 infeciton of mice. In the present study, we focus on macrophages, as more abundant macrophages express the protective cytokine, IFN-γ, than T cells in infected IL-20RA −/− mice.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports of IL-20RA cytokines mostly focused on T cells to show that IL-19 or IL-20 can increase IL-10 and/or decrease IFN-γ to induce T cell polorazation toward a Th2 pro le [19][20][21]. We previously found that T cell responses, especially the Th2 response, promote the production of antibodies, which protect mice from EV-A71 infection [45][46][47], and that the Th2 cytokine IL-6 decreases EV-A71 lethality of mice [30], showing the protective role of Th2 response in EV-A71 infeciton of mice. In the present study, we focus on macrophages, as more abundant macrophages express the protective cytokine, IFN-γ, than T cells in infected IL-20RA −/− mice.…”
Section: Discussionmentioning
confidence: 99%